Selection and the Measured Black-White Wage Gap Among Young Women Revisited - James Albrecht; Aico van Vuuren; Susan Vroman (Institute for the Study of Labor (IZA), 2014)
Derek Neal (JPE 2004) used the NLSY79 to show that the observed median log wage gap between young white and young black women in 1990 underestimated the true, selection-corrected gap, i.e., the gap we would have expected to see had all of these women been employed in 1990. In this paper, we use the NLSY97 to update his analysis. The observed median log wage gap increased substantially between 1990 and 2011, as did the selection-corrected gap. These increases are explained to a considerable extent by changes in the distribution of educational attainment across young white and black women.
Keywords: J15; J16; J31; J71; 330; racial log wage gap; selection; women